2022
DOI: 10.1155/2022/6544705
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Staphylococcus aureus from Milk and Milk Products, Associated Factors for Contamination, and Their Antibiogram in Holeta, Central Ethiopia

Abstract: Staphylococcus aureus is a pathogenic bacterium-contaminating milk and milk products causing food poisoning primarily due to its enterotoxins. The study aimed at estimating the prevalence of S. aureus in milk and milk products, assessing potential risk factors for contamination, and determining the load and the antimicrobial susceptibility profile of the isolates. A cross-sectional study design was employed to collect a total of 486 samples, comprising 383 raw milk, 47 bulk tank milk, 29 curd milk (Ergo), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
34
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 42 publications
10
34
5
1
Order By: Relevance
“…Analysis of multidrug resistance patterns in the current study indicated that 43.94% (29/66) of S. aureus isolates from milk and milk products showed multiple drug resistance. In contrast to this nding, a higher (62.5%) and lower percent (2.4%) of multidrug-resistant S. aureus isolated from milk and milk products were reported by Gebremedhin et al [21] and Regasa et al [63], respectively. The emergence of resistance to numerous drugs represents public health hazard because foodborne outbreaks might be di cult to treat and the group of multidrug resistance S. aureus in the food supply represents a reservoir for communicable resistant genes [62].…”
Section: Antimicrobial Susceptibility Testcontrasting
confidence: 63%
See 2 more Smart Citations
“…Analysis of multidrug resistance patterns in the current study indicated that 43.94% (29/66) of S. aureus isolates from milk and milk products showed multiple drug resistance. In contrast to this nding, a higher (62.5%) and lower percent (2.4%) of multidrug-resistant S. aureus isolated from milk and milk products were reported by Gebremedhin et al [21] and Regasa et al [63], respectively. The emergence of resistance to numerous drugs represents public health hazard because foodborne outbreaks might be di cult to treat and the group of multidrug resistance S. aureus in the food supply represents a reservoir for communicable resistant genes [62].…”
Section: Antimicrobial Susceptibility Testcontrasting
confidence: 63%
“…previously reported resistances from various sources [21,24,31,45]. The existence of an alarming level S.…”
Section: Antimicrobial Susceptibility Testmentioning
confidence: 96%
See 1 more Smart Citation
“…Mastitis is the inflammation of the udder due to the infection of a variety of bacteria that enter the mammary glands and damage them ( 1 ). Mastitis is a serious livestock disease, which usually causes significant economic losses along with clinical and sub-clinical symptoms in highly productive dairy animals ( 2 ). The opportunistic pathogen Staphylococcus aureus ( S. aureus ) is a representative microflora species, which is commonly disseminated on healthy skin and mucous membranes of people and animals ( 3 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, S. aureus is considered the major etiologic pathogen of mastitis in cattle and buffaloes ( 11 ). The infection of S. aureus in dairy cows not only harms the health of animals and milk production or quality ( 2 ) but also potentially transmits this pathogen to herdsmen or citizens ( 9 ).…”
Section: Introductionmentioning
confidence: 99%